2017
DOI: 10.1097/ccm.0000000000002370
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Inflammation into Mortality Risk in Pediatric Acute Respiratory Distress Syndrome

Abstract: Objective In pediatric ARDS, lung injury is mediated by immune activation and severe inflammation. Therefore, we hypothesized that patients with elevated pro- and anti-inflammatory cytokines would have higher mortality rates and that these biomarkers could improve risk-stratification of poor outcomes. Design Multicenter prospective observational study. Setting We enrolled patients from 5 academic PICUs between 2008–2015. Patients Patients were 1 month to 18 years old, used noninvasive or invasive ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…IL-8, a potent neutrophil attractant and activator, was found to be increased in the BALF of patients at risk who ultimately developed ARDS ( 82 ). A multiple logistic regression model incorporating oxygenation index, IL-8, and TNF-R2 was superior in predicting the composite outcome of mortality or severe morbidity ( 83 ). IL-8 plays a significant role in ALI via the formation of anti-IL-8 autoantibody, and IL-8 complexes and of those complexes’ interactions with FcγRIIa receptors, leading to the development of ALI by effecting neutrophil apoptosis ( 84 , 85 ).…”
Section: Il-8mentioning
confidence: 99%
See 1 more Smart Citation
“…IL-8, a potent neutrophil attractant and activator, was found to be increased in the BALF of patients at risk who ultimately developed ARDS ( 82 ). A multiple logistic regression model incorporating oxygenation index, IL-8, and TNF-R2 was superior in predicting the composite outcome of mortality or severe morbidity ( 83 ). IL-8 plays a significant role in ALI via the formation of anti-IL-8 autoantibody, and IL-8 complexes and of those complexes’ interactions with FcγRIIa receptors, leading to the development of ALI by effecting neutrophil apoptosis ( 84 , 85 ).…”
Section: Il-8mentioning
confidence: 99%
“…The role of IL-33 is not limited to Th2 response. By contrast, IL-33 is a potent ( 83 ) activator of group 2 innate lymphoid cells, Th1 cells, Tregs, and CD8 + T cells ( 88 ), and it is an immunostimulatory factor used to induce Treg expansion ( 89 ). It is released in the stage of tissue injury in sepsis and activates type 2 innate lymphoid cells that encourage the polarization of M2 macrophages.…”
Section: Il-33 and Il-18mentioning
confidence: 99%
“…Additional work in PARDS is also underway investigating biomarkers that may better stratify mortality risk and identify targeted treatments for future clinical trials. [91][92][93][94] Beyond these investigations, there remain robust opportunities for prospective study of the effect of various treatment strategies on outcomes in PARDS, including but not limited to ventilatory modes (including airway pressure release ventilation, high-frequency jet ventilation, and neutrally adjusted ventilator assist) and strategies, fluid management, NMB, surfactant in specific populations, steroids, and ECMO.…”
Section: Next Stepsmentioning
confidence: 99%
“…The worst (highest) OI value during the first 3 days of ventilation was the best discriminator for non-survival, with an area under the receiver operating characteristic curve of 0.75 [15]. Recent data suggests that incorporating an inflammatory cytokine profile alongside the oxygenation index is superior in predicting outcomes in pARDS compared to the oxygenation index alone [22]. These data are intriguing, as they suggest the possibility of a future biomarker array that could help identify patients with pARDS at risk for mortality and thus stratify those candidates who should be considered for earlier ECMO support.…”
Section: Hypoxemic Respiratory Failure and Pediatric Acute Respiratormentioning
confidence: 99%
“…Similarly, in Zabrocki's review of pediatric respiratory failure, analysis of pre-ECMO mechanical ventilation revealed that survival remained 56% or higher for children who had ECMO initiated within the first 14 days of mechanical ventilation but declined to 38% beyond this timeframe [24]. Fourteen days is now often considered a "cutoff" for duration of ventilation prior to ECMO; however, the outcomes for patients with certain diagnoses, such as viral pneumonia, can be good even when ECMO is initiated after 2 weeks of ventilation [21,22]. Careful patient selection is therefore paramount to successful use of when ECMO if extracorporeal support is initiated after an extended course of mechanical ventilation.…”
Section: Duration Of Mechanical Ventilationmentioning
confidence: 99%